ACUTE TOXICITY AND ENVIRONMENTAL RISK OF DIFLUBENZURON TO Daphnia magna, Poecilia reticulata AND Lemna minor IN THE ABSENCE AND PRESENCE OF SEDIMENT - DE SOUZA, JAQUELINE PÉROLA; MEDEIROS, LOUISE DE SOUZA; WINKALER, ELISSANDRA ULBRICHT; MACHADO-NETO, JOAQUIM GONÇALVEZ (Pesticidas: Revista de Ecotoxicologia e Meio Ambiente, 2011)
Parasitoses in fish farming are treated by the application of pesticides formulations commonly used in agriculture or veterinary medicine. For the control of ectoparasites, that cause economic losses to the fish production Diflubenzuron is utilized by direct application into water at a 2 mg.L-1 concentration. However, this practice can intoxicate non-target species. This research aimed at determining the acute toxicity of diflubenzuron to Daphnia magna, Poecilia reticulata and Lemna minor; evaluating its environmental risk and defining the role of the sediment in the bioavailability of this insecticide in the water. Results of the study implicate diflubenzuron as being extremely toxic to D. magna. However, no significant toxicity was observed in P. reticulata and L. minor. Bioavailability of this insecticide was significantly reduced by the presence of sediment in the water.